Determinants related to psychological and physiological stress responses in blood donation: A systematic review of scientific production (Research, Society and Development, 2025)
This article presents a systematic review of the scientific literature on the determinants associated with psychological and physiological stress reactions in individuals undergoing blood donation. The analysis was based on articles published between 2021 and 2025, selected from national and international databases, using the PRISMA 2020 protocol as a methodological guide. Studies evaluating variables such as anxiety, fear, hemodynamic changes, and risk perception among voluntary donors were included. The results indicated that most studies identified stress as a relevant factor for adherence and recurrence of blood donation, highlighting the role of psychological interventions and multiprofessional support. It is concluded that stress management strategies, associated with educational and humanization protocols, can reduce adverse responses, enhancing transfusion safety and donor loyalty.